American sailors ashore at Port of Spain, Trinidad, Christmas Day, 1906 - (:unkn) unknown (My University, 2009)
A group of sailors walking through Port of Spain.
Colour: Coloured (hand painted; Style: Landscape; Unbordered,Divided
Keywords: Postcards; Trinidad and Tobago; Sailors--United States; Roads--Trinidad and Tobago; Christmas--Trinidad and Tobago